Some transformations and physicochemical properties of new S-substituted 5-thiophene-(3-ylmethyl)-4R-1,2,4-triazole-3-thiols - A. V. Khilkovets (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Nitrogen-containing heterocyclic compounds are widely represented in modern organic chemistry. A special place among the huge number of substances presented is occupied by derivatives of 1,2,4-triazole due to their uniqueness and prospects. In recent years, these derivatives have remained the object of close attention of both synthetic chemists and researchers engaged in the search for new biologically active substances of a wide spectrum of action, the synthesis of optical materials, dyes, corrosion inhibitors, veterinary drugs, etc. It is known from the literature that the combination of the aromatic heterocycle of thiophene and 1,2,4-triazole is a promising area for research. The result of such combinations is a number of compounds obtained with fairly high yields and a wide range of activities. Thus, further chemical modification of 1,2,4-triazole derivatives by additional administration of a typical thiophene pharmacophore is an urgent task.